Login
Remember
Register
Home
All Activity
Q&A
Questions
Hot!
Unanswered
Tags
Categories
Users
Ask a Question
Ask a Question
`(a – b)^2 = a^2 –
0
votes
asked
Jan 18, 2022
in
8th-maths
by
nikhil
(
1.8k
points)
`(a – b)^2 = a^2 – b^2`
marks1
chapter9
#tnf
Please
log in
or
register
to answer this question.
0
Answers
Categories
All categories
Maths
(8.6k)
12th-maths
(0)
11th-maths
(0)
10th maths
(0)
9th-maths
(0)
8th-maths
(8.6k)
Science
(14)
Physics
(3.4k)
Related questions
`(a + b)^2 = a^2 +
`(a + b) (a – b) = a^2 –
The factors of `a^2 – 2ab + b^2` are (a + b) and (a +
`x^2 + (a + b)x + ab = (a + b) (x +
Factorisation of `– 3a^2 + 3ab + 3ac` is `3a (–a – b –